Multiple Extrasplanchnic Venous Thromboses: A Rare Complication of Pancreatitis. A Case Report - Parikh, Hardik; Shukla, Akash; Aswani, Yashant; Bhatia, Shobna (JOP. Journal of the Pancreas, 2012)
<span style="font-size: 9.0pt; line-height: 115%; font-family: "Times New Roman"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Context<span style="font-size: 9.0pt; line-height: 115%; font-family: "Times New Roman"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> Venous thrombosis has been described in patients with acute and chronic pancreatitis. This is especially common in portal vein, splenic vein and superior mesenteric vein. To the best of our knowledge, involvement of superior vena cava and subclavian vessel due to pancreatitis has not been reported. Case report We present here a case of an adult male with alcoholic chronic pancreatitis who presented with multiple vessel thromboses involving superior vena cava, inferior vena cava, bilateral subclavian, internal jugular vein, axillary, iliac and renal vein without involvement of portal, splenic and superior mesenteric vein that was effectively treated with i.v. anticoagulation therapy. Conclusion Venous thromboses can occur outside the splanchnic circulation in pancreatitis.